Echolocation of bats (Chiroptera Blumenbach, 1779) as an element of their ecological plasticity - E. M. Shchelkanov; S. S. Ukolov; M. N. Dunaeva; T. V. Moskvina; I. A. Popov; Yu. A. Belov; N. N. Kakareka; A. V. Ganzevich; V. F. Tolkach; Yu. G. Volkov; I. V. Galkina; M. Yu. Shchelkanov (Юг России: экология, развитие, 2021)
Aim. The aim of this work was to briefly summarize the current understanding of the phenomenon of echolocation in the order of bats (Chiroptera Blumenbach, 1779).Discussion. The paper discusses: the place of bats among other taxonomic groups of animals that have the ability of echolocation; the history of the discovery of "ear vision" in bats by L. Spallanzani in the 18th century; the first scientifically based assumptions regarding the use of ultrasound by bats and the discovery of this phenomenon in the middle of the last century; methods for emitting and receiving ultrasound by various taxonomic groups of bats; physical patterns underlying the propagation of ultrasonic waves; characteristics of the returned echo and algorithms for echolocation in bats; echolocation interactions between insectivorous bats and nocturnal moths and possibilities for ultrasonic monitoring of bat populations.Conclusion. The inclusion of ultrasound monitoring of bat populations in integrated ecological and virological studies could form a new point of growth in systems to ensure biological security at both national and global levels.